2015
DOI: 10.17759/cpp.2015230402
|View full text |Cite
|
Sign up to set email alerts
|

Modern maturation

Abstract: На материале зарубежных и отечественных исследований обсуждаются про-блемы современного взросления, затрагивающие периоды отрочества, юно-сти и молодости. Показано, что в разных странах существуют разные пред-ставления о том, кого считать взрослым, и что эти представления, равно как и сами маркеры взрослости, заметно изменились за последние десятилетия. В большинстве стран в результате произошедших за последнее время со-цио-культурных изменений наблюдается удлинение периода взросления, который сегодня не тольк… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…The adolescents' problems of self-determination in different life areas are related to the features of this psychological age (Vygotsky, 2000;Leontiev, 1978;Bozhovich, 2009;Elkonin, 1972). The empirical studies done in 2000-2010 confirm the complication of the SSD of modern adolescents, as reflected in the intercorrelation between the adolescents' perception of the nature of success, and their evaluation of own success, their sense of self-esteem (Bukhalenkova & Karabanova, 2018;Konshina & Sadovnikova, 2018;Sobkin & Kalashnikova, 2020), the lengthening of the period of childhood, and infantilism as a common trait representative of modern youth (Martsinkovskaya, 2019;Tolstykh, 2015). The connection between the autonomy of the individual and the motivation for volunteer activities in adolescence is also evident (Molchanov et al, 2022).…”
Section: Introductionmentioning
confidence: 95%
“…The adolescents' problems of self-determination in different life areas are related to the features of this psychological age (Vygotsky, 2000;Leontiev, 1978;Bozhovich, 2009;Elkonin, 1972). The empirical studies done in 2000-2010 confirm the complication of the SSD of modern adolescents, as reflected in the intercorrelation between the adolescents' perception of the nature of success, and their evaluation of own success, their sense of self-esteem (Bukhalenkova & Karabanova, 2018;Konshina & Sadovnikova, 2018;Sobkin & Kalashnikova, 2020), the lengthening of the period of childhood, and infantilism as a common trait representative of modern youth (Martsinkovskaya, 2019;Tolstykh, 2015). The connection between the autonomy of the individual and the motivation for volunteer activities in adolescence is also evident (Molchanov et al, 2022).…”
Section: Introductionmentioning
confidence: 95%
“…A theoretical analysis of scientific literature has shown that on the basis of foreign and domestic modern research, authors discuss family problems [1,2] and carry out studies on changes in the stability and quality of marriage, depending on its duration [3,4]. Currently, most scientists agree that the quality of marriage is multidimensionally dependent on growing up [5], including the periods of childhood, adolescence and youth [6,7]). The authors consider the main positions of scientists regarding the processes of family transformation and its crisis phenomena [8,9].…”
Section: Family As a Socio-psychological Phenomenon And A Necessary Condition For The Development Of Societymentioning
confidence: 99%
“…The "Attractiveness" scale represents the importance of the partner's appearance. Boys got average indicators: it is (6.2) in role expectations and (5,4) in claims, while for girls the indicators are higher: (7,1) in expectations in (6,7) claims. The results showed that the respondents demonstrate a typical young age attitude towards the importance of appearance and its compliance with the standards of modern fashion.…”
mentioning
confidence: 94%
“…[13], Nadasen K. [14], Novak M. [15], Pesina E. [16],Pit S, Byles J. [17], Schlafer M., Shippee T. [18], Schoppe S. [19], Suslova T. [20], Tolstykh N. [21], Torres S. [22], Venn S. [23] and etc. Elderly people are one of the least protected social groups which needs support and help from society and the state.…”
Section: Introductionmentioning
confidence: 99%